A Case Study of National Financial Literacy Programs for Women - Jodi Jarecke; Edward W. Taylor; Tahira Hira (Adult Education Research Conference, 2009)
The purpose of this research study is to explore (case study) in-depth the pedagogy of financial literacy programs for women and how these programs address their educational needs.